Regional development policies modelling: a framework of general equilibrium - Artis Kancs (European Regional Science Association (ERSA), 2001)
The changes the rural economy and society experience today are wide ranging and complex. They stem to a large extent from changing socio-economic norms and values in a society as well as from the changes of the global economy, of the market policy and trade rules. These changes affect however, not only sectoral markets, but local economies and rural areas in general (FERMAN 1999). At the same time rural economies have to meet rising environmental and recreational claims of the society, which fundamentally change both the structure and the level of goods and services demanded from rural economies (DRABENSTOTT and MEEKER 1999). The European Structural Funds as one of the most important rural development policy planning tools in the EU currently undergo a fundamental re-organisation extending the assistance programs towards Central- and Eastern European countries (VANHOVE 1999). These reforms are deep-going and wide-reaching in their nature and influence the competitiveness of rural economies in Europe in several aspects. They will alter the sectoral structure and the activity levels in rural economies as well as the economic performance of these economies in general. In order to be able to consider these economy-wide impacts of a changing institutional framework in the future rural development planning, it is utmost important to assess these a-priori (JOHNSON and SCOTT 1997). Although the ongoing reforms of the regional development policy in the EU play a significant role in changing the rules and conditions of rural economies, there is another obvious influence on the spatial dynamics of an economy, namely the decreasing importance of agriculture in rural economies. Almost all rural areas in Europe have experienced a decline in the importance of agriculture during the nineties so that only very few rural areas could now be defined as being dependent on agruculture. As a result, the economic structure of rural economies dependends more and more on service activities (LOPEZ-BAZO et al. 1999). The role of rural areas has also been altered, particularly in northern Europe, by an increase in the demand for rural 'consumption' goods, for example for rural leisure goods and for rural tourism (EUROPEAN COMMISSION 1999). A further cause for the rapidly changing relationships between actors, sectors and regions in a spatial economy are the changes in production technologies as well as the emergence of completely new production technologies. The Information Technology (IT) branch, one of the most important example of the so called "New Economy" affect economic space and hence rural areas in various ways. The modern tele-commuting technologies e. g. increasingly separate places people live in and work in. This makes it for people more attractive to live rural and to work urban (DRABENSTOTT and MEEKER 1999). One consequence of these changes has been a blurring of the distinctions between rural and urban space and a concomitant change in the nature and the extent of interdependencies that exist between rural and urban areas. From an economic perspective these growing inter-regional interdependencies alter the degree to which income is generated, retained or leaked from a rural or urban economy and the extent to which regions are interdependent (PONS-NOVELL and VILADECANS-MARSAL 1999). The growing inter-regional interdependencies people live in one region, earn money in another one and spend it in a third one), however, have severe consequences in the regions- socio-economic development and, therefore, have to be considered carefully in regional development planning which requires an inter-regional analysis approach (SCHINDLER, ISRAELEVICH, HEWINGS 1997). The main goal of our study is to develop a reliable analysis tool for exploring the impacts of these changing global economic conditions of rural economies. Another objective of our study is to look for alternative rural development planning options and to compare them within the framework of the European Structural Funds in selected applicant countries. While there is little doubt among economists about the increasing importance of these Funds in Europe-s regional economic development, only few of the studies carried out so far have used an inter-regional and inter-sectoral framework to analyse policy impacts to rural and to urban regions as well as to various sectors of an economy explicitly (AZIS 1997a). Using the example of Latvia our study makes a contribution to close this research gap in understanding and predicting the causal structure of the fundamental changes regional economies experience today in Europe as well as to assess the impacts of potential changes in European regional policy setting within a framework of an inter-regional general equilibrium. We have demonstrated in our paper that an inter-regional CGE model can be quite a useful tool for analysing the impacts of changes in global economic conditions and for assessing the inter-regional as well as the inter-sectoral implications of potential policy changes even if computational resources are limited and a full range of regional economic data required by a formal CGE analysis are not available. We have also asserted in our study that a regional CGE model is an impact model permitting analysis of interdependent effects across various parts of an economy rather than a device for statistic testing of economic variables. In our empirical analysis we found out that the rural economy of Latvia, which was used as an example for Central and Eastern European accession countries, has to expect the largest welfare gains from the integration into the EU if Latvia opens its markets gradually and not if the current policy setting is continued or if it conducts a completely liberal market policy as it is favoured by the Chicago School of Economics. This argument is supported by the fact that the market protection in the EU is currently relatively high in comparison to Central and Eastern European countries. Since especially agricultural markets are highly protected in the EU, above all rural regions will gain from the integration to the EU. Moreover, since many of the rural regions in the CEE will be eligible for the financial aid foreseen within the EU Structural Funds these rural communities will be strengthened financially as well.
Keywords: 330